Early-cannulation arteriovenous grafts are safe and effective in avoiding recurrent tunneled central catheter infection. (28th May 2021) - Richarz, S; Stevenson, K; White, B; Thomson, P; Jackson, A; Isaak, A; Kingsmore, D
Abstract: Objective: Tunneled central venous catheter infection (TCVCi) is a common complication that often necessitates removal of the TCVC and a further TCVC. Theoeretically, insertion of an early-cannualtion graft (ecAVG) early after TCVC infection is possible but not widely practiced with concerns over safety and infection in the ecAVG. With 8 years of ecAVG experience, the aim of this study was to compare the outcomes following TCVC infection, comparing replacement with TCVC (TCVCr) versus immediate ecAVG (ecAVGr). Methods: Retrospective comparison of two cohorts, who underwent replacement of an infected TCVC either by an early cannulation graft (n = 18) or by a further central catheter (n = 39). Data were abstracted from a prospectively completed electronic patient record and collected on patient demographics, TCVC insertion, duration and infection, including culture proven bacteriaemia and subsequent access interventions. Results: 18/299 patients identified from 2012-2020 had an ecAVG implanted as treatment for a TCVCi. In a one-year time-period (1/1/2015 -31/12/2015) out of 222 TCVC inserted, 39 were as a replacement following a TCVCi. No patient with an ecAVGr developed an immediate infection, nor complication from the procedure. The rate of subsequent vascular access infection was significantly more frequent for those with TCVCr than with an ecAVGr (0.6 vs. 0.1/patient/ 1000 HD days, p < 0.000). The number of further TCVC required was significantly higher in the TCVCr group (7.1 vs. 0.4/patient/ 1000 HD days, p = 0.000). Conclusion: An ecAVG early following a TCVC infection is safe, reduces the incidence of subsequent infectious complications and reduces the number of TCVC required, with a better functional patency.